Pengaruh Model Pembelajaran Moral Reasoning dan Inquiry Terhadap Hasil Belajar Santri Pada Bidang Studi Aqidah Akhlak - Mohamad Faturohman; Naf'an Torihoran; Nana Suryapermana (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to see the effect of the moral reasoning and inquiry learning model. The subjects of this study were students of grade 3 MTs Daar el-Qolam 1. This type of research is a causal correlational study with an ex-post facto approach. In grade 3 students at MTs Daar el-Qolam 1 as respondents, totaling 371 students with a sample of 55 students taken randomly, with variable X1 (moral reasoning learning model) and variable X2 (inquiry learning model) with variable Y (learning outcomes aqidah morals). The research instrument for data collection was using a questionnaire (test) for variables X1, X2 and Y. Before the instrument was used, a trial was conducted on 30 students of class 3 MTs Daar el-Qolam 1 to determine the validity and reability of the research instrument, data analysis techniques used used is simple regression analysis and multiple regression analysis with a significant level α= 0.05. The results show that this is indicated by the regression equation, multiple linear regression analysis Y= 11.62 + 0. 454X1 + 0.211X2, the correlation coefficient (R) is 0.766 and the determination coefficient (R2) is 0.587% from the F result of 36,975. The Learning Model of Moral reasoning and Inquiry has a positive effect on learning outcomes of moral aqidah. It can be stated (Ha) has been accepted, there is an effect of the learning model of moral reasoning and inquiry on the learning outcomes of students in the field of aqidah akhlak study.